Perioperative severe airway hemorrhage during veno-arterial extracorporeal membrane oxygenation for acute massive pulmonary embolism - Kun Cao; Feng Hai (Medicine, 2026)
Rationale: According to the 2019 ERS/ESC guidelines, high-risk pulmonary embolism is defined as a case that presents with hemodynamic instability, obstructive shock, or cardiac arrest, and this condition has an extremely high death rate. ECMO can provide temporary circulatory support, acting as a bridge to definitive reperfusion therapy. Patient Concerns: The patient is a 25-year-old woman who had previously used estrogen-containing oral contraceptives. She sustained trauma to her right lower limb, necessitating prolonged immobilization. One month before her symptoms started, she had a high fever. One hour before she was admitted to the hospital, she fainted and went into cardiac arrest. Ten minutes of cardiopulmonary resuscitation were needed before her spontaneous circulation returned. Diagnoses: The electrocardiography test showed an S 1 Q 3 T 3 pattern. An ultrasonography check confirmed thrombosis in the right popliteal vein. Transthoracic echocardiography found that the right heart was enlarged, and the left ventricle had a D shape. Computed tomography pulmonary angiography showed a saddle embolus right at the bifurcation of the pulmonary artery, which confirmed acute massive pulmonary embolism (MPE). Interventions: The patient was supported with veno-arterial extracorporeal membrane oxygenation (VA-ECMO), followed by catheter-directed thrombolysis and targeted airway hemostasis. Urokinase was administered through 2 thrombolysis catheters, and anticoagulation was adjusted dynamically according to bleeding and coagulation status. Outcomes: After the procedure, airway bleeding was stopped using targeted hemostasis methods, and the patient was able to come off ECMO successfully after 73 hours of use. Lessons: In this case, we achieved successful support from VA-ECMO for a patient with acute MPE. Our work shows that even severe bleeding in the airway can be handled safely, and you don’t have to stop anticoagulation treatment to do it. This approach ended up with the patient making a full recovery in the end.